Chain dynamics and intermolecular association in dilute aqueous solutions of isotactic and atactic Poly(Methacrylic acid): Effect of NaCl concentration. (12th June 2019) - Sitar, Simona; Aseyev, Vladimir; Žagar, Ema; Kogej, Ksenija
Abstract: Dynamic and static light scattering measurements were performed on isotactic and atactic forms of poly (methacrylic acid), iPMA and aPMA, respectively, in order to perform a wide survey of their molecular properties and chain dynamics in water as functions of tacticity, degree of neutralization, α N, and salt concentration, c s . The molecular parameters of PMA chains were analyzed at low α N and chain dynamics (diffusion coefficients and in this connection the polyelectrolyte slow mode behavior) at higher α N . The data revealed that both PMAs form microgel-like aggregates with a core-shell structure at low α N (= 0 and 0.25 for aPMA and iPMA, respectively). The distribution of the hydrophilic and hydrophobic functional groups within the aggregates and their compactness depended considerably on chain tacticity and for aPMA also on c s . Further, the effect of c s on the polyelectrolyte slow diffusion coefficient, D s, of partly (0.25 ≤  α N  < 1) or completely charged PMA polyions ( α N  = 1) was studied. In iPMA solutions, D s was detected up to c s  = 0.1 M, regardless of α N, whereas in aPMA solutions this c s value gradually decreased with decreasing α N . These differences were also related to tacticity and through that to rigidity of the studied forms of PMA. It is argued that the segregation of uncharged and charged carboxyl groups is operative over the entire α N region in iPMA solutions. Graphical abstract: Image 1